Microsoft office Excel 2007 step by step - Frye, Curtis D. (Microsoft Press, 2007)
Excel provides an easy-to-use, powerful spreadsheet environment that helps you handle calculations and data more effectively - with simple ways to enter and edit data, work with formulas and functions for complex calculations, format worksheets and work with colorful charts, and publish documents to the Web. With MICROSOFT EXCEL 2007 STEP BY STEP, you'll learn all the ins and outs of working with Excel features, including the exciting new interface for this latest version of Office. This information-packed guide provides numbered steps and hands-on examples that show you how to get the most out of Excel. With this book, you'll learn how to work with tools to make worksheet entry faster, make your Excel documents more attractive, present information visually with charts, sorting and filtering data, publish documents on the Web, and lots more. The companion CD provides all exercise source files so that you get hands-on with Excel right away.